A Pragmatic Analysis Of Slogan Used In Car Advertisement - Inderagiri, Ashar Waskito; , Drs. H. Maryadi, MA; , Dra. Siti Zuhriah Ariatmi, M. Hum (2013)
This research is aimed at describing the linguistic forms and meanings of each slogan used in car advertisement. This research is descriptive qualitative research. The object this research is the slogan used in car advertisement. The data are slogans that are in the form of word, phrase, clause and sentence of car advertisement slogan that only slogan from a car made in Japan taken from internet, television, car brochures, magazine and newspaper. In collecting the data, the writer uses a documentation method by selecting and writing the slogans which is found in internet, television, car brochures, magazine and newspaper. In finding out the linguistic forms of the slogans, the writer uses structural grammar. In describing the meaning of the slogans, the writer uses pragmatic analysis especially speech act theory. Based on the analysis, the researcher finds the data based on the linguistics form of the slogan 3 (6,12%) data of noun, 1 (2,04%) datum of adjective, 20 (40,82%) data of noun phrase, 3 (6,12) data of verb phrase, 1 (2,04%) datum of adjective phrase, 1 (2,04%) datum of adverb phrase, 1 (2,04%) datum of gerund phrase, 8 (16,33%) data of declarative sentence, 1 (2,04%) datum of interrogative sentence and 10 (20,41%) data of imperative sentence). Based on the meaning of the slogan, the researcher finds 24 (48,98%) data of asserting, 12 (24,49%) data of commanding, 9 (18,37%) data of persuading and 4 (8,16%) data of informing.